Pengembangan Bahan ajar transformasi geometri berbantuan website: Pendekatan Project-Based-Learning Mozaik Geometri - Gusni Satriawati; Nur Kholis; Gelar Dwirahayu; Dindin Sobiruddin (JINoP (Jurnal Inovasi Pembelajaran), 2023)
The digital era positively impacts all aspects of life, including education. Current learning requires teachers to use technology. Technology in learning mathematics is needed, especially in geometry material. The basic concept in geometry is the ability to visualize. An excellent understanding of visualization will help students understand geometric concepts. This study aims to develop teaching materials for geometry transformation material assisted by a website with a project-based learning approach using a geometric mosaic model that the eligibility criteria for teaching materials; therefore, it can be used in teaching and learning. Research and development with the ADDIE model are conducted in this study, which consists of phases:  Analysis, Design, Development, Implementation, and Evaluation. The instruments used were expert/practitioner content validation sheets and student construct validation sheets; the instrument was developed using seven aspects. Teaching materials are validated by experts and also assessed by students. Based on the results of the assessment of 7 experts/experts, it was shown that the geometry transformation teaching material obtained very appropriate criteria with an assessment percentage of 85%. In contrast, the assessment of 28 Al Hasra Depok High School students showed good criteria with an assessment percentage value of 80%. Therefore, researchers can recommend website-assisted geometry transformation teaching materials using a project-based learning approach, "geometry mosaic," which can complement existing teaching materials and be used in mathematics learning activities, especially at the high school level.